Letramento : a leitura inferencial dos gêneros numa perspectiva sociointeracionista - Luna, Natasha Ferraz Canto Pessoa de (2012)
This dissertation presents a study on the expansion of reading through approach genres. We observe, in public schools in Pernambuco state in which the project was developed intervention, that reading is not worked properly since there is a dynamic incentive to read, much less a work directed in the classroom so that actually reading part of a routine school context. What happens is decontextualized Portuguese language classes, in which grammatical rules are the absolute protagonists and language acquisition. In view of this, it was confirmed in the school field of study of this project, there is still much difficulty in making the student to appropriate reading. Relying on this, the research focused on primary reading strategies with a view to literacy, in other words, to encourage reading and bring to the classroom. The challenge we set ourselves was to make a group of elementary school students in a public school reading development in its many dimensions from the perspective of gender approach sociointeractionist through a qualitative research. To work with reading, the study of gender becomes paramount in the construction of the strategies of language, since the subject is part and participant of sociodiscursives processes that occur in your community. Given this, we had a breakthrough as a result of this group in the acquisition of literacy, seen through the progress of the Portuguese language classes in school (reported by current teachers of these students), and positive results in tests such as the Saepe, where diversity of the genera composing and reading all the evidence.